Lung-Derived Selectins Enhance Metastatic Behavior of Triple Negative Breast Cancer Cells - Sami U. Khan; Ying Xia; David Goodale; Gabriella Schoettle; Alison L. Allan (Biomedicines, 2021)
The lung is one of the deadliest sites of breast cancer metastasis, particularly for triple negative breast cancer (TNBC). We have previously shown that the lung produces several soluble factors that may enhance the metastatic behavior of TNBC, including E-, L-, and P-selectin. In this paper, we hypothesize that lung-derived selectins promote TNBC metastatic behavior and may serve as a potential therapeutic target. Lungs were isolated from mice and used to generate lung-conditioned media (CM). Lung-derived selectins were immunodepleted and TNBC migration and proliferation were assessed in response to native or selectin-depleted lung-CM. A 3D ex vivo pulmonary metastasis assay (PuMA) was used to assess the metastatic progression of TNBC in the lungs of wild-type versus triple-selectin (ELP-/-) knockout mice. We observed that individual lung-derived selectins enhance in vitro migration (p ≤ 0.05), but not the proliferation of TNBC cells, and that ex vivo metastatic progression is reduced in the lungs of ELP-/- mice compared to wild-type mice (p ≤ 0.05). Treatment with the pan-selectin inhibitor bimosiamose reduced in vitro lung-specific TNBC migration and proliferation (p ≤ 0.05). Taken together, these results suggest that lung-derived selectins may present a potential therapeutic target against TNBC metastasis. Future studies are aimed at elucidating the pro-metastatic mechanisms of lung-derived selectins and developing a lung-directed therapeutic approach.